SOROGAN VS BANDONGAN AS METHOD OF ARABIC LANGUAGE TEACHING DAKWAH MODEL IN ISLAMIC BOARDING SCHOOL: A SYSTEMATIC LITERATURE REVIEW - Ma'ruf, Ma'ruf; Nova Irawati , Sutiyah; Fitriyanti, Nur; Kusuma Wardhana, Akhmad (Tanfidziya: Journal of Arabic Education, 2025)
The sorogan and bandongan methods can facilitate effective Arabic teaching in Islamic boarding schools. This study aims to see the challenges, things that need to be prepared, and the potential of sorogan and bandongan as Arabic teaching methods for congregations in Islamic boarding schools. This study uses a systematic literature review (SLR) with sample paper data taken from the Scopus website. There are 46 document data taken from 1990-2025. The data were analyzed using SLR to find out what is needed and the obstacles to implementing the sorogan and bandongan methods. The results of the study show that Bandongan emphasizes memorization more while Sorogan emphasizes understanding and interaction. In addition, Sorogan is suitable for extroverts while bandongan is suitable for introverts. The practical implications of this study can be a reference for things that need to be prepared in teaching Arabic to students in Islamic boarding schools.